2012
DOI: 10.1002/joc.3521
|View full text |Cite
|
Sign up to set email alerts
|

Canadian RCM projected changes to short‐ and long‐term drought characteristics over the Canadian Prairies

Abstract: ABSTRACT:The Canadian Prairies have experienced severe and extended droughts that have had significant impacts on agriculture, energy and other socio-economic sectors; it is therefore desirable to assess future changes to drought characteristics in this drought prone region, in the context of a changing climate. This study addresses validation and projected changes to short-and long-term drought characteristics, i.e. severity, frequency and duration, over the Canadian Prairies, using an ensemble of ten Canadia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 36 publications
3
24
0
Order By: Relevance
“…CESM-LE is a 30-member ensemble, run under the Representative Concentration Pathway 8.5 (RCP 8.5) to the year 2080. In this study we assume that the model bias is stationary in time (Buonomo et al 2007;Done et al 2013;PaiMazumder et al 2013;PaiMazumder and Done 2014). We examine changes to PDSI by looking at future anomalies, i.e., we calculate each ensemble member's mean PDSI for the control period and subtract that from each member.…”
Section: Inmentioning
confidence: 99%
See 1 more Smart Citation
“…CESM-LE is a 30-member ensemble, run under the Representative Concentration Pathway 8.5 (RCP 8.5) to the year 2080. In this study we assume that the model bias is stationary in time (Buonomo et al 2007;Done et al 2013;PaiMazumder et al 2013;PaiMazumder and Done 2014). We examine changes to PDSI by looking at future anomalies, i.e., we calculate each ensemble member's mean PDSI for the control period and subtract that from each member.…”
Section: Inmentioning
confidence: 99%
“…their own climate. Because of their smaller domain and higher resolution, RCMs can resolve finer scale physical processes and enhance the representation of land surface characteristics, leading to improved simulation of smaller scales (Dickinson et al 1989;Giorgi et al 1994;Wang et al 2004;Lo et al 2008;Heikkila et al 2010;Maraun et al 2010;Qian et al 2009;PaiMazumder et al 2013;Harding et al 2013). However, these dynamical models remain expensive and therefore limited in their use, especially in terms of running ensembles to make an assessment of the uncertainty from internal variability at local scales.…”
Section: Introductionmentioning
confidence: 99%
“…The Intergovernmental Panel on Climate Change [10] has concluded that climate change has begun to affect the frequency, intensity and duration of extreme events such as extreme temperatures, extreme precipitation, droughts, etc. For Southern Prairies, an analysis of projected changes to precipitation and drought characteristics between the1971-2000 and 2041-2070 periods suggests a decrease in mean precipitation in summer and an increase for the other seasons, whereas the severity, frequency and maximum duration of both short-and long-term droughts are projected to increase, with the largest projected changes associated with longer drought events [11].…”
Section: Impact Of Extreme Eventsmentioning
confidence: 99%
“…Drought severity for 3-month (DRO3), 6-month (DRO6) and 10-month (DRO10) durations for the Canadian Prairies were simulated with the CRCM for the A2 scenario, 2041-2070 period (PaiMazumder et al 2012). These are based on drought severity indices obtained from accumulated monthly precipitation deficits, using 1971-2000 reference climatology.…”
mentioning
confidence: 99%